Análise da evolução do sistema de coleta seletiva nas macrorregiões nordeste e sudeste do Brasil - Faccioli, Gabriela (2019)
With the current demand growing for material goods considered disposable, production has wildly increased, and the lifetime has been shortened, thus, creating a major challenge: proper management of solid waste. One of the alternatives used is recycling. Selective collection aims to organize the discarded waste to make its reuse or recycling more efficient. With Law 12.305 / 2010, became basic right the waste management in municipalities. This paper used two data platforms, SNIS - National Systems of Sanitation Information and CEMPRE - Business Commitment for Recycling, to analyze and compare data about the selective collection growth in the two largest macro-regions of Brazil, Northeast and Southeast. The data show that there was a real growth regarding selective collection, however, the Northeast region still lacks this practice in its municipalities. The fact is that the city halls should take more information and invest in environmental education, so that it is possible to build new habits from sensitizing and awareness of the population.